Dynamic behavior of Dengue and Zika viruses NS1 protein reveals monomer–monomer interaction mechanisms and insights to rational drug design. Issue 14 (21st September 2020) - Gonçalves, Ricardo Lemes; de Lima Menezes, Gabriela; Sussuchi, Luciane; Moreli, Marcos Lázaro; Mottin, Melina; Andrade, Carolina Horta; Pereira, Maristela; da Silva, Roosevelt Alves
Abstract : Communicated by Ramaswamy H. Sarma